How chest press-based exercises can alleviate the burden of cardiovascular diseases - Stefano Palermi; Nicola L. Bragazzi; Drazen Cular; Luca P. Ardigò; Johnny Padulo (Termedia Publishing House, 2021)
Unlike in the previous decades, strength training is gaining more scientific attention owing to its numerous benefits on human health. It has major benefits on metabolic processes, cardiovascular system, musculoskeletal system, age-related processes, and mental health. In comparison with aerobic low-intensity exercises, chest press-based strength training cardiovascular adaptations have been ignored for many years. Yet, if properly prescribed and conducted, strength training has shown to be safe and effective in people with cardiovascular disease. This narrative review aims at summarizing the available evidence about the role of chest press-based strength training on the cardiovascular system.